Targeting Gastrointestinal Cancers with Carvacrol: Mechanistic Insights and Therapeutic Potential - Nitika Patwa; Gagandeep Singh; Vikas Sharma; Priyanka Chaudhary; Bunty Sharma; Shafiul Haque; Vikas Yadav; Shakti Ranjan Satapathy; Hardeep Singh Tuli (Biomolecules)
Gastrointestinal (GI) cancers, including esophageal, gastric, pancreatic, liver, and colorectal malignancies, represent a major global health burden due to their high incidence, aggressive nature, and limited treatment outcomes. This review explores the therapeutic potential of carvacrol, a naturally occurring monoterpenoid phenol predominantly found in oregano and other aromatic plants. Carvacrol has demonstrated strong anticancer properties by modulating multiple molecular pathways governing apoptosis, inflammation, angiogenesis, and metastasis. Preclinical studies have revealed its ability to selectively target cancer cells while sparing healthy tissue. Advances in nanotechnology have further enhanced its pharmacological profile by improving solubility, stability, and tumor-targeted delivery. Additionally, carvacrol shows synergistic effects when used in combination with conventional chemotherapeutics. While the evidence is promising, clinical studies are needed to validate its translational potential. This review aims to consolidate current findings and encourage further investigation into carvacrol’s application as an adjunct or alternative therapeutic agent in GI cancer management.